La violencia de género En el ámbito laboral - Sánchez Trigueros, Carmen (Revista de Derecho, 2019)
Gender violence at work takes place in two different ways: sexual harassment and harassment based on gender. The latter is a phenomenon which has recently been recognized as such, and thus it has barely been studied as a discriminatory behavior or as a manifestation of gender violence at work. Everything that has been said up to this point affects the Social Security sphere, on which the present study is focused. The reason why the Social Security sphere is the main focus of the study is due to the doctrinal and judicial treatments that harassment at work (in any of its specific forms) has had since a contingency can be classified as an accident at work.